Isolation of multidrug-resistant Escherichia coli, Staphylococcus spp., and Streptococcus spp. from dogs in Chattogram Metropolitan Area, Bangladesh (Journal of Advanced Veterinary and Animal Research, 2020)
Objectives: Antibacterial resistance is a great concern in human and food animal medicine, and it poses a significant concern in pet animals like dogs. This cross-sectional study was conducted to evaluate the antimicrobial resistance pattern of Escherichia coli, Staphylococcus spp., and Streptococcus spp. along with the carryover of some resistance genes in E. coli from dogs in the Chattogram metropolitan area, Bangladesh.  Materials and Methods: Rectal swab (n = 50), nasal swab (n = 50), and skin swab (n = 50) samples were collected from dogs having respiratory infections, skin infections, and/or enteritis, respectively. Three types of bacteria were identified and isolated by conventional bacteriological techniques and biochemical tests. Antimicrobial susceptibility testing was carried out against 12 antimicrobials by disk diffusion methods. Six resistance genes, namely blaTEM, blaCTX-M, tetA, tetB, Sul-I, and Sul-II, were screened for phenotypically resistant E. coli isolates by the polymerase chain reaction.  Results: A total of 39 (78%) E. coli, 25 (50%) Staphylococcus spp., and 24 (48%) Streptococcus spp. isolates were isolated from the rectal swab, nasal swab, and skin swab samples, respectively. In the cultural sensitivity test, the E. coli isolates showed resistance to ceftriaxone (79%) and sulfamethoxazole/trimethoprim (64%). Doxycycline (80%) demonstrated the highest resistance among Staphylococcus isolates, followed by sulfamethoxazole/trimethoprim (60%). Streptococcus isolates showed the highest resistance to penicillin (63%), followed by ceftriaxone (54%), while no isolate showed resistance to gentamycin. The prevalence of blaTEM, blaCTX-M, tetA, tetB, Sul-I, and Sul-II genes in phenotypically resistant E. coli isolates were 100%, 61.29%, 100%, 8.33%, 56%, and 72%, respectively.Conclusions: Spillover of such multidrug-resistant bacteria and resistance genes from pet dogs pose a serious public health risk.J. Adv. Vet. Anim. Res., 7(4): 669-677, Dec 2020http://doi.org/10.5455/javar.2020.g466